Analisis Logam Ni, Mn dan Cr pada Air dan Sedimen di Perairan Pantai Pulau Singkep Kepulauan Riau - Alimah Alimah; Yusni Ikhwan Siregar; Bintal Amin (Dinamika Lingkungan Indonesia, 2014)
Analysis of Ni, Mn and Cr concentrations in seawater and sediment in Singkepisland coastal waters has been conducted in March 2014. All water quality parametersmeasured were still within the tolerable limits for the survival of the aquatic organisms.Samples of sea water and sediment were taken from five stations with three replicates at eachstation. Heavy metals concentrations were analyzed in the Marine Chemistry LaboratoryFaculty of Fisheries and Marine Sciences, University of Riau by using Atomic Absorption3110 Perkin Elmer spectrophotometer. The results showed that the average concentration ofheavy metals in Singkep waters are 0.1820; 0.1084 and 0.4133 μg/L for Ni, Mn and Cr inwater, whilst in sediment are 13.2615, 13.7261 and 81.4578 μg/g for Ni, Mn and Cr. Simplelinear regression analysis indicates positive correlation between Ni in sea water and insediment with y = 10,42 + 22,19x, r = 0,138 and negative correlation with y = 15,09 -13,44xr = 0,226 for Mn and y = 104,8 - 50,76x, r = 0.354 for Cr.